Turf soil enhances treatment efficiency and performance of phenolic wastewater in an up-flow anaerobic sludge blanket reactor. (August 2018) - Chen, Chunmao; Yao, Xianyang; Li, Qing X.; Wang, Qinghong; Liang, Jiahao; Zhang, Simin; Ming, Jie; Liu, Zhiyuan; Deng, Jingmin; Yoza, Brandon A.
Abstract: Phenols are industrially generated intermediate chemicals found in wastewaters that are considered a class of environmental priority pollutants. Up-flow anaerobic sludge blanket (UASB) reactors are used for phenolic wastewater treatment and exhibit high volume loading capability, favorable granule settling, and tolerance to impact loads. Use of support materials can promote biological productivity and accelerate start-up period of UASB. In the present study, turf soil was used as a support material in a mesophilic UASB reactor for the removal of phenols in wastewater. During sludge acclimatization (45–96 days), COD and phenols in the treatments were both reduced by 97%, whereas these contents in the controls were decreased by 81% and 75%, respectively. The phenol load threshold for the turf soil UASB reactor was greater (1200 mg/L, the equivalent of COD 3000 mg/L) in comparison with the control UASB reactor (900 mg/L, the equivalent of COD 2250 mg/L) and the turf soil UASB reactor was also more resistant to shock loading. Improved sludge settling, shear resistance, and higher biological activity occurred with the turf soil UASB reactor due to the formation of large granular sludge (0.6 mm or larger) in higher relative percentages. Granular sludge size was further enhanced by the colonization of filamentous bacteria on the irregular surface of the turf soil. Highlights: Turf soil was novel used in a UASB reactor for phenolic wastewater treatment. Turf soil improved performance and resilience to impact loading. Bigger granules were formed with better settling property with turf soil. Humic substances in turf soil facilitated phenol biodegradation. Rough surface and mesopores provided habitat for bacteria growth.